PENGARUH GAYA KEPEMIMPINAN TRANFORMASIONAL DAN TRANSAKSIONAL TERHADAP KOMITMEN ORGANISASI: Studi Pada SMK Pawyatan Daha 3 Kediri - Sumaryati, Sri Ari; Dina, Nur; Sumarsono, Erik (Universitas Pawyatan Daha, 2023)
This study aims to determine the effect of transformational leadership style and transactional transformational leadership style on organizational commitment. This research method uses a quantitative approach by distributing questionnaires that are entered to obtain objective data on variable factors, namely transformational leadership style, transactional leadership style and organisational commitment. The population and sample in this study were 66 employees who worked at SMK Pawyatan Daha 3 Kediri. The results showed that simultaneously the effect between transformational leadership style and transactional leadership style on organisational commitment, transformational leadership style has a more dominant influence than transactional leadership style.